Research on Evaluation Index System of Emergency Scheduling Scheme for Reservoir with Loss of Regulation Capacity and Its Application in Xijiang River - REN Mengzhi; LIU Dengfeng; YANG Yuanyuan; LIU Dong; HUANG Qiang; WAN Xin (Renmin Zhujiang)
Events of reservoir with loss of regulation capacity include failure of reservoir tostore water or discharge water due to abnormal operation of discharge structures. Emergencyscheduling of reservoir with loss of regulation capacity can effectively reduce the adverseimpact. This paper establishes an evaluation index system for extreme events such as completefailure of reservoir to store or discharge water, with the criteria layer including reservoirsafety, water supply, power generation and ecology and the index layer including the durationratio of reservoir over-check water level, ratio of maximum change range of reservoir water level,ratio of water supply guarantee, vulnerability of water supply, maximum water shortage rate,minimum output ratio, loss of power generation benefits, ratio of time to meet ecological flow andthe satisfaction degree of ecological flow; assigns the weight to each index by analytic hierarchyprocess (AHP); and evaluates the different schemes for reservoirs in Xijiang River Basin underfour loss of regulation capacity scenarios with the fuzzy optimization model, non-negative matrixfactorization algorithm and AGA-based projection pursuit clustering model. The results show thatthere is a slight difference in the advantages and disadvantages of the schemes evaluated bydifferent methods, and the recommended schemes under different scenarios are given by integratingthe three methods.